Perancangan Strategi Pemasaran Galeri Investasi Berdasarkan Faktor-faktor yang Mempengaruhi Intensi Investor untuk Berinvestasi - Sari, Hasrini; Pradana, Muhammad Rifky Adi (Jurnal Ilmiah Teknik Industri, 2018)
Investment gallery is a three parties collaboration, between IDX, securities company, and university that aims to increase the number of investors, especially from the civitas academica. However, in the past year, more than 50% Investment galleries failed to meet the growing investor target. Therefore, it is necessary to redesign an investment gallery that is more oriented to the wants and needs of investors and potential investors. through investment galleries and their intention to reinvest. Factors are generated through literature studies and interviews to customers and management of IDX and results in 12 factors. These factors were measured by 32 indicators and tested using an online and offline questionnaire of 193 respondents from 7 best investment galleries in Indonesia. The data obtained is processed by using factor analysis so as to form 5 factors: perceived image, customer experience, benefit, facilities, and response time. These results are then processed to see the relationship of each factor to the intention to re-invest. Based on multiple linear regression analysis, only 4 factors have significant effect, which are perceived image, benefit, facilities, and customer experience. The results of the study were then used to develop an investment gallery marketing strategy.